2021
DOI: 10.1186/s12978-021-01178-9
|View full text |Cite
|
Sign up to set email alerts
|

Sexual and reproductive health of Syrian refugee adolescent girls: a qualitative study using focus group discussions in an urban setting in Lebanon

Abstract: Background The war in Syria caused the forced displacement of millions of Syrians to neighboring countries. Lebanon is the host country with the largest overall number of Syrian refugees per capita. Adolescent refugee girls experience a unique level of vulnerability during human emergencies and are at increased risk of suffering from poor sexual and reproductive health (SRH) outcomes. We conducted an exploratory qualitative study to learn about the SRH perceptions and experiences of refugee ado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 62 publications
2
18
0
Order By: Relevance
“…Our results were concordant with a study conducted by the United Nations Population Fund (UNFPA) found that one-third of SR women in Lebanon between the ages of 20-24 were married before the age of 18 [19]. Similar results were reported in other studies conducted in Lebanon, Jordan and Turkey as well [20][21][22]. Prior to the crisis in Syria, child marriage took place among 13% of girls under the age of 18, but since then, forced displacement has led to a major increase in this number [23][24][25].…”
Section: Discussionsupporting
confidence: 92%
“…Our results were concordant with a study conducted by the United Nations Population Fund (UNFPA) found that one-third of SR women in Lebanon between the ages of 20-24 were married before the age of 18 [19]. Similar results were reported in other studies conducted in Lebanon, Jordan and Turkey as well [20][21][22]. Prior to the crisis in Syria, child marriage took place among 13% of girls under the age of 18, but since then, forced displacement has led to a major increase in this number [23][24][25].…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, studies found that girls lacked adequate knowledge on the frequency of changing their pads and its disposal method ( 35 , 36 , 39 , 40 ). Participants also noted the problems they had while attempting to use disposable pads efficiently for the first time because of insufficient guidance ( 44 ). Due to lack of space and bin for disposal of menstrual products, some bury or flush their used pads ( 35 , 45 ).…”
Section: Resultsmentioning
confidence: 99%
“…Women had difficulty locating private spaces within their shelters to change, wash, and dry their reusable clothes ( 18 , 39 ). As a result, they had to use their menstrual products for long hours comprising hygiene and could change it while going for open defecation or bathing near water bodies or shrubs in the early morning or late at night ( 39 , 44 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations